2022
DOI: 10.3389/fimmu.2022.1027064
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Aflatoxin B1 attenuates immune function of immune organs in grass carp (Ctenopharyngodon idella) by modulating NF-κB and the TOR signaling pathway

Abstract: Aflatoxin B1 (AFB1) is kind of a common mycotoxin in food and feedstuff. Aquafeeds are susceptible to contamination of AFB1. In teleost fish, the spleen and head kidney are key immune organ. Moreover, the fish skin is a critical mucosal barrier system. However, there was little study on the effects of dietary AFB1 on the immune response of these immune organs in fish. This study aimed to explore the impacts of oral AFB1 on the immune competence and its mechanisms in the skin, spleen, and head kidney of grass c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Research conducted on tilapia has demonstrated that diets containing AFB1 can impede fish growth by causing damage to the intestines [ 45 ]. Similarly, grass carp showed necrosis, immune cell infiltration, and fibrous hyperplasia in intestinal tissue with increasing AFB1 levels in their diet [ 46 ]. In Chinese sea bass, different concentrations of AFB1 led to varying degrees of blurring and damage to the tightly connected structures of the fish intestine, with clear gaps and vacuolation of cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted on tilapia has demonstrated that diets containing AFB1 can impede fish growth by causing damage to the intestines [ 45 ]. Similarly, grass carp showed necrosis, immune cell infiltration, and fibrous hyperplasia in intestinal tissue with increasing AFB1 levels in their diet [ 46 ]. In Chinese sea bass, different concentrations of AFB1 led to varying degrees of blurring and damage to the tightly connected structures of the fish intestine, with clear gaps and vacuolation of cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed that AFB1 caused oxidative damage in zebrafish muscle ( He et al., 2023b ). Moreover, AFB1 induced inflammatory response through upregulating gene expression related to proinflammatory cytokines in grass carp head kidney ( He et al., 2022 ), and proinflammatory cytokines could activate JNK signaling molecule ( López-Bergami et al., 2005 ). Thus, we hypothesized that AFB1 might activate uPA and MMP through p38MAPK and p-JNK signaling pathways, degrade ECM, and thus inhibit muscle development of grass carp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory found that the content of collagen Ⅰ in fish was regulated by transforming growth factor-β (TGF-β)/Smads signaling pathway ( Dong et al., 2022 ). It was reported that AFB1 downregulated TGF-β mRNA levels in skin of grass carp ( He et al., 2022 ). Thus, AFB1 might reduce the levels of collagen through TGF-β/Smads signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…10 The excessive inflammation caused by AFB 1 may be linked to the triggering of the nuclear factor-κB (NF-κB) signaling pathway. 11 Meanwhile, AFB 1 has been found to upregulate the expression of pro-inflammatory cytokines, including interleukin (IL)-1β, IL-2, and IL-6. 12 Furthermore, AFB 1 disrupts lymphocyte proliferation, impairs the immune function, and damages the spleen tissue.…”
Section: Introductionmentioning
confidence: 99%